La evaluación en el proceso de interaprendizaje de los estudiantes del 8º año de educación general básica de la Unidad Educativa Ana Páez, de la ciudad de Latacunga - Pichucho Aymacaña, Jenny Alexandra (2016)
This present research has the structure of a methodological guide of techniques and assessment instruments, with the purpose of giving a contribution on the application of inputs that demonstrate the learning of an adequate way. The assessment is a determinant factor in the diagnosis of achievements of educational aims. In addition, this one helps to optimize the inter learning process, considering that it is a constant, permanent, systematic and organized process that it needs of a previous planning to achieve the educational proposed goals. Therefore, at the beginning of a topic or a pre-established activity during the hour class or academic year….